FACTORS AFFECTING SUCCESSFUL IMPLEMENTATION OF INFORMATION TECHNOLOGY PROJECTS: EXPERTS’ PERCEPTION - Cosmas Ifeanyi Nwakanma; Baldwin Chukwunanu Asiegbu; Chibueze Achimba Ogbonna; Peter-Paul Chukwuemezie Njoku (European Scientific Journal, ESJ, 2013)
﻿The alarming rate of Information Technology (IT) project, and business failure, even globally, remains a major concern to stakeholders, especially clients, in developing countries like Nigeria where infrastructure per capita is known to be low. In order to survive, firms depend on the implementation of new IT ideas with their capital intensive nature, and a major objective of reducing time-to-market for the private sector, and increased social benefit for the public sector. Using data from experts in the industry in Nigeria, this paper presents an ordinal profile of factors contributing to successful project implementation and the extent of the contribution based on variance analysis, and regression models. It was discovered at the end of the study that six factors namely clear requirements and specification, clear objective and goal, realistic schedule, effective project management methods/skills, support from top management and user/client involvement have collective effect on implementation of IT-Projects in Nigeria. It was further deduced that the most critical factor is realistic schedule while the least is clear objective and goals. The predictive model developed accounted for 62.9% effect of these factors on Implementation of IT-Projects in Nigeria.